Supercritical gas foaming material and preparation method thereof

The durability and antibacteriality of existing materials are solved by mixing polyethylene terephthalate pellets, modified silica and modified silsesquioxane and molding foaming. The problem of insufficient performance achieves the long-term and efficient antibacterial effect of the material.

CN119410020APending Publication Date: 2025-02-11ALPHA (GUANGDONG) HIGH-TECH MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411722529.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing supercritical gas foaming materials have poor durability and antibacterial properties, which leads to aging, reducing comfort during use, and prone to breeding bacteria and fungi, resulting in foot odor problems.

Method used

The supercritical gas foamed material was prepared by mixing polyethylene terephthalate pellets, modified silica and modified silsesquioxane. Modified silsesquioxane is made by premodification and reaction, and has anti-aging properties; modified silica is made by reaction of flame retardant pyrrole monomer and pyrrole, and has good flame retardant and antibacterial properties.

Benefits of technology

It improves the durability and antibacterial ability of supercritical gas foaming materials, extends the service life of the materials, reduces the breeding of bacteria and fungi, and reduces the occurrence of foot odor problems.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a supercritical gas foaming material and a preparation method thereof, and relates to the field of high polymer materials. When the supercritical gas foaming material is prepared, (3-iodopropyl) trimethoxysilane is prepared into pre-modified silsesquioxane, and then the pre-modified silsesquioxane sequentially reacts with sodium azide and 1-hydroxyacetylene to prepare modified silsesquioxane; the preparation method comprises the following steps: sequentially reacting trimethoxysilane with 1-allyl-1H-pyrrole and nano silicon dioxide to prepare pre-modified silicon dioxide; the preparation method comprises the following steps: reacting 1-allyl-1H-pyrrole with phosphorous acid to prepare a flame-retardant pyrrole monomer; reacting a flame-retardant pyrrole monomer, pyrrole and the pre-modified silicon dioxide to obtain modified silicon dioxide; and mixing polyethylene glycol terephthalate granules, the modified silicon dioxide and the modified silsesquioxane, and carrying out mould pressing foaming to obtain the supercritical gas foaming material. The supercritical gas foaming material prepared by the invention has excellent antibacterial, anti-aging, flame-retardant and antistatic effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer materials, in particular to a supercritical gas foaming material and a preparation method thereof. Background Art

[0002] Foam plastics contain a large number of bubbles, which not only saves raw materials but also improves impact resistance and heat insulation performance. In recent decades, the foam plastics industry has developed rapidly at home and abroad, especially in the fields of packaging, construction and transportation. With the advancement of science and technology, various new types of foaming materials and foaming methods are constantly emerging. Polyethylene terephthalate foam material, as a new type of foam plastic, has begun to enter people's lives.

[0003] Supercritical gas foam materials are also used to make insoles, but the durability of insoles is usually relatively poor. Due to the material and structural characteristics of air cushion insoles, after a period of use, the cushioning effect and comfort will decrease due to aging. In addition, some insole materials have weak sweat absorption properties and are prone to breed bacteria and fungi, leading to foot odor problems. Therefore, this article introduces a supercritical gas foam material with aging resistance and antibacterial capabilities. Summary of the invention

[0004] The purpose of the present invention is to provide a supercritical gas foaming material and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] A supercritical gas foaming material, wherein the supercritical gas foaming material is prepared by mixing polyethylene terephthalate pellets, modified silicon dioxide and modified silsesquioxane and performing molding and foaming;

[0006] The modified silsesquioxane is prepared by preparing pre-modified silsesquioxane with (3-iodopropyl)trimethoxysilane, and then reacting with sodium azide and 1-hydroxyacetylene in sequence;

[0007] The modified silicon dioxide is prepared by reacting a flame retardant pyrrole monomer, pyrrole, and pre-modified silicon dioxide;

[0008] The pre-modified silica is prepared by reacting trimethoxysilane with 1-allyl-1H-pyrrole and nano-silica in sequence;

[0009] The flame retardant pyrrole monomer is prepared by reacting 1-allyl-1H-pyrrole with phosphorous acid.

[0010] A method for preparing a supercritical gas foam material, the method for preparing a supercritical gas foam material mainly comprising the following preparation steps:

[0011] (1) Tetramethyl sodium hydroxide, isopropanol, (3-iodopropyl)trimethoxysilane and xylene are mixed in a mass ratio of 0.3-0.4:3-5:2-3:5-7, stirred at 70-90°C and 200-300 r / min for 50-70 min, cooled to room temperature, the upper layer of liquid is taken, and vacuum dried at -10-0°C for 22-26 h to obtain pre-modified silsesquioxane; diazotized silsesquioxane, 1-hydroxyacetylene, tert-butyl silylene are mixed, and the mixture is ...200-300 r / min for 50-70 min, and the mixture is cooled to room temperature, the upper layer of liquid is taken, and vacuum dried at -10-0°C for 22-26 h to obtain pre-modified silsesquioxane; diazotized silsesquioxane, 1-hydroxyacetylene, tert-butyl silylene are mixed, and the mixture is stirred at 200-300 r / min for 50-70 min, and the mixture is stirred at 200-300 r / min for 50-70 min, and the mixture is stirred at 200-300 r / min for 50-70 min, and the mixture is cooled to room temperature, the upper layer of liquid is taken, and the upper layer of liquid is vacuum dried at -10-0°C for 22-26 h, and Butanol, deionized water, copper sulfate pentahydrate and sodium ascorbate are mixed in a molar ratio of 1:8.6-9:14-16:14-16:0.08-0.12:0.1-0.3, reacted for 8-12 hours at 26-30°C and 50-70 r / min under nitrogen protection, dried for 6-8 hours at 80-90°C, washed with deionized water for 3-5 times, and vacuum dried for 22-26 hours at -10-0°C to obtain modified silsesquioxane;

[0012] (2) trimethoxysilane and 1-allyl-1H-pyrrole are mixed in a molar ratio of 1:1, a catalyst of 0.03 to 0.05 times the mass of methyldimethoxysilane is added, and the mixture is reacted at 60 to 70°C for 4 to 6 hours to obtain modified siloxane; flame retardant pyrrole monomer, pyrrole, pre-modified silica, ethanol and deionized water are mixed in a mass ratio of 1:3 to 5:6 to 8:2 to 4:10 to 14, stirred at 200 to 300 r / min for 8 to 10 minutes, filtered, and dried at 40 to 60°C for 22 to 26 hours to obtain modified silica;

[0013] (3) Polyethylene terephthalate pellets, modified silica and modified silsesquioxane are uniformly mixed in a mass ratio of 8 to 12:1:1, vacuum dried at 100 to 120° C. for 11 to 13 hours, placed in a tablet press, and pressed into polyethylene terephthalate sheets at 260 to 280° C. The polyethylene terephthalate sheets are vacuum dried at 100 to 110° C. for 10 to 14 hours, placed in a mold, and carbon dioxide is introduced. Two-dimensional restricted foaming is performed at 225 to 245° C. and 10 to 16 MPa for 8 to 12 minutes to obtain foamed polyethylene terephthalate.

[0014] As an optimization, the diazotized silsesquioxane in step (1) is prepared by mixing pre-modified silsesquioxane, sodium azide, and an aqueous solution of N,N-dimethylformamide with a mass fraction of 68 to 72% in a mass ratio of 1:0.3 to 0.5:4 to 6, stirring at 50 to 70°C and 100 to 200 r / min for 22 to 26 hours, and vacuum drying at -10 to 0°C for 22 to 26 hours.

[0015] As an optimization, the catalyst in step (2) is prepared by uniformly mixing chloroplatinic acid and isopropanol in a mass ratio of 1:75-82.

[0016] As an optimization, the flame retardant pyrrole monomer in step (2) is prepared by mixing 1-allyl-1H-pyrrole and phosphorous acid in a molar ratio of 1:1, placing the mixture in a high pressure reactor, and reacting the mixture at 115-125° C. for 10-12 hours.

[0017] As an optimization, the pre-modified silica in step (2) is prepared by uniformly mixing nano-silica, modified siloxane and isopropanol in a mass ratio of 1:1:6-8, stirring for 5-7 hours at 85-95°C and 200-300 r / min, centrifuging, washing with deionized water for 3-5 times, and drying at 90-100°C for 2-4 hours.

[0018] As an optimization, the polyethylene terephthalate sheet in step (3) has a thickness of 0.8 to 1.2 mm.

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0020] When preparing the supercritical gas foaming material, the present invention prepares (3-iodopropyl) trimethoxysilane into pre-modified silsesquioxane, and then reacts with sodium azide and 1-hydroxyacetylene in sequence to obtain modified silsesquioxane; trimethoxysilane reacts with 1-allyl-1H-pyrrole and nano silicon dioxide in sequence to obtain pre-modified silicon dioxide; 1-allyl-1H-pyrrole reacts with phosphorous acid to obtain flame-retardant pyrrole monomer; flame-retardant pyrrole monomer, pyrrole and pre-modified silicon dioxide are reacted to obtain modified silicon dioxide; polyethylene terephthalate pellets, modified silicon dioxide and modified silsesquioxane are mixed, and molded and foamed to obtain the supercritical gas foaming material.

[0021] First, (3-iodopropyl)trimethoxysilane is prepared into pre-modified silsesquioxane, which is then reacted with sodium azide and 1-hydroxyacetylene in sequence to obtain modified silsesquioxane; silsesquioxane is not easily affected by ultraviolet rays and visible light and has good anti-aging properties; the imidazole loaded on the silsesquioxane can inhibit the growth of fungal cells and thus play an antibacterial role, and the hydroxyl group on the imidazole can achieve a better bonding effect with the phosphate group on the modified silica and the polyethylene terephthalate pellets.

[0022] Secondly, trimethoxysilane is reacted with 1-allyl-1H-pyrrole and nano-silica in sequence to obtain pre-modified silica; 1-allyl-1H-pyrrole is reacted with phosphorous acid to obtain a flame-retardant pyrrole monomer; phosphorus contained in the flame-retardant monomer can generate phosphorus-containing free radicals, which can capture hydrogen free radicals and hydroxyl free radicals in the flame area, interrupt the polymer combustion chain reaction and thus slow down the combustion, and can generate polymetaphosphoric acid with a stable structure and low volatility during the combustion process. Polymetaphosphoric acid has a strong dehydration effect, and during the heating process, the polymer is carbonized into a dense and flame-retardant carbonized layer, and the carbonized layer covers the surface of the polymer, isolates the bottom material from contact with external oxygen, and hinders the external heat from being transferred to the base material, thereby effectively preventing the material from further pyrolysis and terminating the combustion of the material, thereby improving the flame retardancy of the material.

[0023] Finally, the flame retardant pyrrole monomer, pyrrole and pre-modified silica are reacted to obtain modified silica; polyethylene terephthalate pellets, modified silica and modified silsesquioxane are mixed and molded and foamed to obtain a supercritical gas foaming material. Polypyrrole can produce non-flammable gas, which can dilute the concentration of oxygen in the air and combustibles produced by thermal decomposition of the polymer on the one hand, and the nitrogen oxides produced by the decomposition can capture free radicals, inhibit the chain reaction of the polymer, and improve the flame retardancy of the material on the other hand. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] Example 1

[0026] A method for preparing a supercritical gas foaming material mainly comprises the following preparation steps:

[0027] (1) Tetramethyl sodium hydroxide, isopropanol, (3-iodopropyl) trimethoxysilane and xylene were mixed in a mass ratio of 0.3:3:2:5, stirred at 70°C and 200 r / min for 50 min, cooled to room temperature, the upper layer of liquid was taken, and vacuum dried at -10°C for 22 h to obtain pre-modified silsesquioxane; diazotized silsesquioxane, 1-hydroxyacetylene, tert-butyl alcohol, deionized water, copper sulfate pentahydrate and sodium ascorbate were mixed in a molar ratio of 1:8.6:14:14:0.08:0.1, reacted at 26°C and 50 r / min for 8 h under nitrogen protection, dried at 80°C for 6 h, washed with deionized water 3 times, and vacuum dried at -10°C for 22 h to obtain modified silsesquioxane;

[0028] (2) trimethoxysilane and 1-allyl-1H-pyrrole were mixed in a molar ratio of 1:1, a catalyst of 0.03 times the mass of methyldimethoxysilane was added, and the mixture was reacted at 60°C for 4 hours to obtain modified siloxane; flame retardant pyrrole monomer, pyrrole, pre-modified silica, ethanol and deionized water were mixed in a mass ratio of 1:3:6:2:10-14, stirred at 200 r / min for 8 minutes, filtered, and dried at 40°C for 22 hours to obtain modified silica;

[0029] (3) Polyethylene terephthalate pellets, modified silica and modified silsesquioxane are uniformly mixed in a mass ratio of 8:1:1, vacuum dried at 100°C for 11 hours, placed in a tablet press, and pressed into polyethylene terephthalate sheets at 260°C. The polyethylene terephthalate sheets are vacuum dried at 100°C for 10 hours, placed in a mold, and carbon dioxide is introduced. Two-dimensional restricted foaming is carried out at 225°C and 10 MPa for 8 to 12 minutes to obtain foamed polyethylene terephthalate.

[0030] Example 2

[0031] A method for preparing a supercritical gas foaming material mainly comprises the following preparation steps:

[0032] (1) Tetramethyl sodium hydroxide, isopropanol, (3-iodopropyl) trimethoxysilane and xylene were mixed in a mass ratio of 0.35:4:2.5:6, stirred at 80°C and 250 r / min for 60 min, cooled to room temperature, the upper layer of liquid was taken, and vacuum dried at -5°C for 24 h to obtain pre-modified silsesquioxane; diazotized silsesquioxane, 1-hydroxyacetylene, tert-butyl alcohol, deionized water, copper sulfate pentahydrate and sodium ascorbate were mixed in a molar ratio of 1:8.8:15:15:0.1:0.2, reacted under nitrogen protection at 28°C and 60 r / min for 10 h, dried at 85°C for 7 h, washed with deionized water 4 times, and vacuum dried at -5°C for 24 h to obtain modified silsesquioxane;

[0033] (2) trimethoxysilane and 1-allyl-1H-pyrrole were mixed in a molar ratio of 1:1, a catalyst of 0.04 times the mass of methyldimethoxysilane was added, and the mixture was reacted at 65°C for 5 hours to obtain modified siloxane; flame retardant pyrrole monomer, pyrrole, pre-modified silica, ethanol and deionized water were mixed in a mass ratio of 1:4:7:3:12, stirred at 250 r / min for 9 minutes, filtered, and dried at 50°C for 24 hours to obtain modified silica;

[0034] (3) Polyethylene terephthalate pellets, modified silica and modified silsesquioxane are uniformly mixed in a mass ratio of 10:1:1, vacuum dried at 110°C for 12 hours, placed in a tablet press, and pressed into polyethylene terephthalate sheets at 270°C. The polyethylene terephthalate sheets are vacuum dried at 105°C for 12 hours, placed in a mold, and carbon dioxide is introduced. Two-dimensional restricted foaming is carried out at 235°C and 13 MPa for 10 minutes to obtain foamed polyethylene terephthalate.

[0035] Example 3

[0036] A method for preparing a supercritical gas foaming material mainly comprises the following preparation steps:

[0037] (1) Tetramethyl sodium hydroxide, isopropanol, (3-iodopropyl) trimethoxysilane and xylene were mixed in a mass ratio of 0.4:5:3:7, stirred at 90°C and 300 r / min for 70 min, cooled to room temperature, the upper layer of liquid was taken, and vacuum dried at 0°C for 26 h to obtain pre-modified silsesquioxane; diazotized silsesquioxane, 1-hydroxyacetylene, tert-butyl alcohol, deionized water, copper sulfate pentahydrate and sodium ascorbate were mixed in a molar ratio of 1:9:16:16:0.12:0.3, reacted at 30°C and 70 r / min for 12 h under nitrogen protection, dried at 90°C for 8 h, washed with deionized water 5 times, and vacuum dried at 0°C for 26 h to obtain modified silsesquioxane;

[0038] (2) trimethoxysilane and 1-allyl-1H-pyrrole were mixed in a molar ratio of 1:1, a catalyst of 0.05 times the mass of methyldimethoxysilane was added, and the mixture was reacted at 60-70°C for 4-6 hours to obtain modified siloxane; flame retardant pyrrole monomer, pyrrole, pre-modified silica, ethanol and deionized water were mixed in a mass ratio of 1:5:8:4:14, stirred at 300 r / min for 10 minutes, filtered, and dried at 60°C for 26 hours to obtain modified silica;

[0039] (3) Polyethylene terephthalate pellets, modified silica and modified silsesquioxane are uniformly mixed in a mass ratio of 12:1:1, vacuum dried at 120°C for 13 hours, placed in a tablet press, and pressed into polyethylene terephthalate sheets at 280°C. The polyethylene terephthalate sheets are vacuum dried at 110°C for 14 hours, placed in a mold, and carbon dioxide is introduced. Two-dimensional restricted foaming is carried out at 245°C and 16 MPa for 12 minutes to obtain foamed polyethylene terephthalate.

[0040] Comparative Example 1

[0041] A method for preparing a supercritical gas foaming material mainly comprises the following preparation steps:

[0042] (1) Tetramethyl sodium hydroxide, isopropanol, (3-iodopropyl)trimethoxysilane and xylene were mixed in a mass ratio of 0.35:4:2.5:6, stirred at 80°C and 250 r / min for 60 min, cooled to room temperature, the upper layer of liquid was taken, and vacuum dried at -5°C for 24 h to obtain pre-modified silsesquioxane;

[0043] (2) trimethoxysilane and 1-allyl-1H-pyrrole were mixed in a molar ratio of 1:1, a catalyst of 0.04 times the mass of methyldimethoxysilane was added, and the mixture was reacted at 65°C for 5 hours to obtain modified siloxane; flame retardant pyrrole monomer, pyrrole, pre-modified silica, ethanol and deionized water were mixed in a mass ratio of 1:4:7:3:12, stirred at 250 r / min for 9 minutes, filtered, and dried at 50°C for 24 hours to obtain modified silica;

[0044] (3) Polyethylene terephthalate pellets, modified silica and pre-modified silsesquioxane are mixed uniformly in a mass ratio of 10:1:1, vacuum dried at 110°C for 12 hours, placed in a tablet press, and pressed into polyethylene terephthalate sheets at 270°C. The polyethylene terephthalate sheets are vacuum dried at 105°C for 12 hours, placed in a mold, and carbon dioxide is introduced. Two-dimensional restricted foaming is carried out at 235°C and 13 MPa for 10 minutes to obtain foamed polyethylene terephthalate.

[0045] Comparative Example 2

[0046] A method for preparing a supercritical gas foaming material mainly comprises the following preparation steps:

[0047] (1) trimethoxysilane and 1-allyl-1H-pyrrole were mixed in a molar ratio of 1:1, a catalyst of 0.04 times the mass of methyldimethoxysilane was added, and the mixture was reacted at 65°C for 5 hours to obtain modified siloxane; flame retardant pyrrole monomer, pyrrole, pre-modified silica, ethanol and deionized water were mixed in a mass ratio of 1:4:7:3:12, stirred at 250 r / min for 9 minutes, filtered, and dried at 50°C for 24 hours to obtain modified silica;

[0048] (2) Polyethylene terephthalate pellets and modified silica were mixed uniformly in a mass ratio of 10:1, vacuum dried at 110°C for 12 hours, placed in a tablet press, and pressed into polyethylene terephthalate sheets at 270°C. The polyethylene terephthalate sheets were vacuum dried at 105°C for 12 hours, placed in a mold, and carbon dioxide was introduced. Two-dimensional restricted foaming was performed at 235°C and 13 MPa for 10 minutes to obtain foamed polyethylene terephthalate.

[0049] Comparative Example 3

[0050] A method for preparing a supercritical gas foaming material mainly comprises the following preparation steps:

[0051] (1) Tetramethyl sodium hydroxide, isopropanol, (3-iodopropyl) trimethoxysilane and xylene were mixed in a mass ratio of 0.35:4:2.5:6, stirred at 80°C and 250 r / min for 60 min, cooled to room temperature, the upper layer of liquid was taken, and vacuum dried at -5°C for 24 h to obtain pre-modified silsesquioxane; diazotized silsesquioxane, 1-hydroxyacetylene, tert-butyl alcohol, deionized water, copper sulfate pentahydrate and sodium ascorbate were mixed in a molar ratio of 1:8.8:15:15:0.1:0.2, reacted under nitrogen protection at 28°C and 60 r / min for 10 h, dried at 85°C for 7 h, washed with deionized water 4 times, and vacuum dried at -5°C for 24 h to obtain modified silsesquioxane;

[0052] (2) trimethoxysilane and 1-allyl-1H-pyrrole were mixed in a molar ratio of 1:1, a catalyst of 0.04 times the mass of methyldimethoxysilane was added, and the mixture was reacted at 65°C for 5 hours to obtain modified siloxane; pyrrole, pre-modified silica, ethanol and deionized water were mixed in a mass ratio of 4:7:3:12, stirred at 250 r / min for 9 minutes, filtered, and dried at 50°C for 24 hours to obtain modified silica;

[0053] (3) Polyethylene terephthalate pellets, modified silica and modified silsesquioxane are uniformly mixed in a mass ratio of 10:1:1, vacuum dried at 110°C for 12 hours, placed in a tablet press, and pressed into polyethylene terephthalate sheets at 270°C. The polyethylene terephthalate sheets are vacuum dried at 105°C for 12 hours, placed in a mold, and carbon dioxide is introduced. Two-dimensional restricted foaming is carried out at 235°C and 13 MPa for 10 minutes to obtain foamed polyethylene terephthalate.

[0054] Comparative Example 4

[0055] A method for preparing a supercritical gas foaming material mainly comprises the following preparation steps:

[0056] (1) Tetramethyl sodium hydroxide, isopropanol, (3-iodopropyl) trimethoxysilane and xylene were mixed in a mass ratio of 0.35:4:2.5:6, stirred at 80°C and 250 r / min for 60 min, cooled to room temperature, the upper layer of liquid was taken, and vacuum dried at -5°C for 24 h to obtain pre-modified silsesquioxane; diazotized silsesquioxane, 1-hydroxyacetylene, tert-butyl alcohol, deionized water, copper sulfate pentahydrate and sodium ascorbate were mixed in a molar ratio of 1:8.8:15:15:0.1:0.2, reacted under nitrogen protection at 28°C and 60 r / min for 10 h, dried at 85°C for 7 h, washed with deionized water 4 times, and vacuum dried at -5°C for 24 h to obtain modified silsesquioxane;

[0057] (2) Polyethylene terephthalate pellets and modified silsesquioxane were mixed uniformly in a mass ratio of 10:1, vacuum dried at 110°C for 12 hours, placed in a tablet press, and pressed into polyethylene terephthalate sheets at 270°C. The polyethylene terephthalate sheets were vacuum dried at 105°C for 12 hours, placed in a mold, and carbon dioxide was introduced. Two-dimensional restricted foaming was carried out at 235°C and 13 MPa for 10 minutes to obtain foamed polyethylene terephthalate.

[0058] Test Example 1

[0059] Flame retardancy test

[0060] The limiting oxygen index was tested according to GBT / 2406 test standard. The results are shown in Table 1.

[0061] Table 1

[0062] Limiting oxygen index Example 1 29.8% Example 2 29.7% Example 3 29.9% Comparative Example 1 29.7% Comparative Example 2 27.1% Comparative Example 3 24.8% Comparative Example 4 21.3%

[0063] From the comparison of the experimental data in Table 1, it can be found that the supercritical gas foamed material prepared in the present invention has good flame retardancy.

[0064] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3 in Table 1, it can be found that the limiting oxygen index of Examples 1, 2, 3 is larger than that of Comparative Example 3, which shows that the phosphorus contained in polypyrrole can generate phosphorus-containing free radicals, which can capture hydrogen free radicals and hydroxyl free radicals in the flame area, interrupt the polymer combustion chain reaction to slow down the combustion, and generate polymetaphosphoric acid with stable structure and non-volatile in the combustion process. Polymetaphosphoric acid has a strong dehydration effect, which promotes the carbonization of the polymer into a dense and flame-retardant carbonized layer during heating. The carbonized layer covers the surface of the polymer, isolates the bottom material from contact with external oxygen, and hinders the external heat from being transferred to the base material, thereby effectively preventing the material from further pyrolysis and terminating the combustion of the material, improving the flame retardancy of the material, and increasing the limiting oxygen index of the material;

[0065] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4, it can be found that the limiting oxygen index of Examples 1, 2, 3 is larger than that of Comparative Example 4, which shows that polypyrrole can produce non-combustible gas, which can dilute the concentration of oxygen in the air and combustibles produced by thermal decomposition of the polymer on the one hand, and the nitrogen oxides produced by decomposition can capture free radicals, inhibit the chain reaction of the polymer, improve the flame retardancy of the material, and increase the limiting oxygen index of the material.

[0066] Test Example 2

[0067] Antimicrobial testing

[0068] The test was carried out according to the GB / T20944 oscillation method, wherein the selected bacterial species was Candida albicans. The results are shown in Table 2.

[0069] Table 2

[0070] Candida albicans Example 1 99.8% Example 2 99.7% Example 3 99.8% Comparative Example 1 78.9% Comparative Example 2 72.2% Comparative Example 3 99.8% Comparative Example 4 99.7%

[0071] From the comparison of the experimental data in Table 2, it can be found that the supercritical gas foaming material prepared by the present invention has good antibacterial ability.

[0072] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1 in Table 2, it can be found that the antibacterial rates of Examples 1, 2, 3 are higher than those of Comparative Example 1, which indicates that imidazole can inhibit the growth of fungal cells and thus play an antibacterial role.

[0073] Test Example 3

[0074] Anti-aging test

[0075] Anti-aging test: The material was made into a sample strip with a length of 10 mm, a width of 4 mm, and a thickness of 1 mm, and the tensile performance test was carried out. The tensile breaking strength was tested at 5 mm / min. The same sample strip was irradiated under a fluorescent ultraviolet lamp UV-A340 for 15 days, and the tensile breaking strength was tested. The tensile breaking strength retention rate was calculated, where the tensile breaking strength retention rate = tensile breaking strength after aging / tensile breaking strength after aging*100%. The results are shown in Table 3.

[0076] Table 3

[0077] Tensile break retention rate Example 1 97.8% Example 2 98.2% Example 3 98.1% Comparative Example 1 98.0% Comparative Example 2 94.9% Comparative Example 3 98.3% Comparative Example 4 97.9%

[0078] From the comparison of the experimental data in Table 3, it can be found that the supercritical gas foamed material prepared in the present invention has good anti-aging ability.

[0079] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2 in Table 3, it can be found that the fracture retention rates of Examples 1, 2, 3 are greater than those of Comparative Example 2, which indicates that silsesquioxane is not easily affected by ultraviolet rays and visible light and has good anti-aging properties.

[0080] Test Example 4

[0081] Antistatic test

[0082] The sample to be tested was cut into a size of 100×100×2 mm and the surface resistivity was tested. The results are shown in Table 4.

[0083] Table 4

[0084] Surface resistivity Example 1 1.138+E12ohm Example 2 1.135+E12ohm Example 3 1.137+E12ohm Comparative Example 1 1.130+E12ohm Comparative Example 2 1.133+E12ohm Comparative Example 3 1.136+E12ohm Comparative Example 4 1.876+E15ohm

[0085] From the comparison of the experimental data in Table 4, it can be found that the supercritical gas foamed material prepared in the present invention has good antistatic ability.

[0086] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4, it can be found that the surface resistivity of Examples 1, 2, 3 is lower than that of Comparative Example 4, which shows that polypyrrole, as a conductive polymer, can absorb and disperse static charges, thereby reducing the accumulation of static electricity, achieving an antistatic effect, and reducing the surface resistivity of the material.

[0087] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A supercritical gas foaming material, characterized in that: The supercritical gas foaming material is prepared by mixing polyethylene terephthalate pellets, modified silicon dioxide and modified silsesquioxane and performing molding and foaming. The modified silsesquioxane is prepared by preparing pre-modified silsesquioxane with (3-iodopropyl)trimethoxysilane, and then reacting with sodium azide and 1-hydroxyacetylene in sequence; The modified silicon dioxide is prepared by reacting a flame retardant pyrrole monomer, pyrrole, and pre-modified silicon dioxide; The pre-modified silica is prepared by reacting trimethoxysilane with 1-allyl-1H-pyrrole and nano-silica in sequence; The flame retardant pyrrole monomer is prepared by reacting 1-allyl-1H-pyrrole with phosphorous acid.

2. A method for preparing a supercritical gas foaming material, characterized in that: The preparation method of the supercritical gas foaming material mainly includes the following preparation steps: (1) Tetramethyl sodium hydroxide, isopropanol, (3-iodopropyl)trimethoxysilane and xylene are mixed in a mass ratio of 0.3-0.4:3-5:2-3:5-7, stirred at 70-90°C and 200-300 r / min for 50-70 min, cooled to room temperature, the upper layer of liquid is taken, and vacuum dried at -10-0°C for 22-26 h to obtain pre-modified silsesquioxane; diazotized silsesquioxane, 1-hydroxyacetylene, tert-butyl silylene are mixed, and the mixture is ...200-300 r / min for 50-70 min, and the mixture is cooled to room temperature, the upper layer of liquid is taken, and vacuum dried at -10-0°C for 22-26 h to obtain pre-modified silsesquioxane; diazotized silsesquioxane, 1-hydroxyacetylene, tert-butyl silylene are mixed, and the mixture is stirred at 200-300 r / min for 50-70 min, and the mixture is stirred at 200-300 r / min for 50-70 min, and the mixture is stirred at 200-300 r / min for 50-70 min, and the mixture is cooled to room temperature, the upper layer of liquid is taken, and the upper layer of liquid is vacuum dried at -10-0°C for 22-26 h, and Butanol, deionized water, copper sulfate pentahydrate and sodium ascorbate are mixed in a molar ratio of 1:8.6-9:14-16:14-16:0.08-0.12:0.1-0.3, reacted for 8-12 hours at 26-30°C and 50-70 r / min under nitrogen protection, dried for 6-8 hours at 80-90°C, washed with deionized water for 3-5 times, and vacuum dried for 22-26 hours at -10-0°C to obtain modified silsesquioxane; (2) trimethoxysilane and 1-allyl-1H-pyrrole are mixed in a molar ratio of 1:1, a catalyst of 0.03 to 0.05 times the mass of methyldimethoxysilane is added, and the mixture is reacted at 60 to 70°C for 4 to 6 hours to obtain modified siloxane; flame retardant pyrrole monomer, pyrrole, pre-modified silica, ethanol and deionized water are mixed in a mass ratio of 1:3 to 5:6 to 8:2 to 4:10 to 14, stirred at 200 to 300 r / min for 8 to 10 minutes, filtered, and dried at 40 to 60°C for 22 to 26 hours to obtain modified silica; (3) Polyethylene terephthalate pellets, modified silica and modified silsesquioxane are uniformly mixed in a mass ratio of 8 to 12:1:1, vacuum dried at 100 to 120° C. for 11 to 13 hours, placed in a tablet press, and pressed into polyethylene terephthalate sheets at 260 to 280° C. The polyethylene terephthalate sheets are vacuum dried at 100 to 110° C. for 10 to 14 hours, placed in a mold, and carbon dioxide is introduced. Two-dimensional restricted foaming is performed at 225 to 245° C. and 10 to 16 MPa for 8 to 12 minutes to obtain foamed polyethylene terephthalate.

3. The method for preparing a supercritical gas foaming material according to claim 2, characterized in that: The diazotized silsesquioxane in step (1) is prepared by mixing pre-modified silsesquioxane, sodium azide, and an aqueous solution of N,N-dimethylformamide with a mass fraction of 68-72% in a mass ratio of 1:0.3-0.5:4-6, stirring at 50-70°C and 100-200 r / min for 22-26 hours, and vacuum drying at -10-0°C for 22-26 hours.

4. The method for preparing a supercritical gas foaming material according to claim 2, characterized in that: The catalyst in step (2) is prepared by uniformly mixing chloroplatinic acid and isopropanol in a mass ratio of 1:75-82.

5. The method for preparing a supercritical gas foamed material according to claim 2, characterized in that: The flame retardant pyrrole monomer in step (2) is prepared by mixing 1-allyl-1H-pyrrole and phosphorous acid in a molar ratio of 1:1, placing the mixture in a high pressure reactor, and reacting the mixture at 115-125° C. for 10-12 hours.

6. The method for preparing a supercritical gas foamed material according to claim 2, characterized in that: The pre-modified silica in step (2) is prepared by uniformly mixing nano-silica, modified siloxane and isopropanol in a mass ratio of 1:1:6-8, stirring at 85-95°C and 200-300 r / min for 5-7 hours, centrifuging, washing with deionized water for 3-5 times, and drying at 90-100°C for 2-4 hours.

7. The method for preparing a supercritical gas foamed material according to claim 2, characterized in that: The polyethylene terephthalate sheet in step (3) has a thickness of 0.8 to 1.2 mm.

Citation Information

Patent Citations

  • Preparation method of cotton fabric with electrical conductivity, electromagnetic shielding and flame-retardant functions

    CN105369600A

  • Flame retardant type PET resin composition

    CN106832813A

  • PET for foaming, PET foamed material and preparation method of foamed material

    CN110551277A

  • Flame-retardant PET (Polyethylene Terephthalate) material and preparation method thereof

    CN115895206A

  • Supercritical foaming PET (Polyethylene Terephthalate) material and preparation method thereof

    CN116041917A